ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PENDIDIKAN DI KABUPATEN KEPAHIANG - Rahmat Al Hidayat; Praptosumo Praptosumo (STIESNU Bengkulu, 2021)
Abstract Kepahiang Regency has a HDI value in 2016 of 66.35 below the Bengkulu Province average of 69.33. One of the determining components of the Kepahiang Regency's HDI is the education index. The education index value of Kepahiang Regency in 2015 was still low at 59.23.The objectives of this study are analyze the influence of BOS fund, dependency ratios, and the ratio teachers students to the education index in Kepahiang District. That data used in this research are secondary data from 2010 until 2015. The tool of analyzeused was panel data regressionin the application program Eviews 10.The results of the panel data regression use the common effect model method, it can be concluded that BOS fund had positive and significant effect, dependency ratios and the ratio teachers students had negative and significant on the education index in Kepahiang District. Keywords: education index, BOS fund, dependency ratios, the ratio teachers students, panel data regression